Effects of Ladder-Climbing Exercise on Mammary Cancer: Data from a Chemically Induced Rat Model - Jessica Silva; Tiago Azevedo; Inês Aires; Catarina Medeiros; Maria J. Neuparth; Fernanda Seixas; Rita Ferreira; Ana I. Faustino-Rocha; Paula A. Oliveira; José Alberto Duarte (Veterinary Sciences)
Breast cancer remains a significant global health issue, affecting both humans and companion animals, particularly female dogs and cats, where mammary tumors are among the most common cancers. Strategies to minimize the impact of this disease on patients, pet owners, and veterinary medicine are essential. This study analyses the effects of resistance training on the development of chemically induced mammary cancer in female Wistar rats, divided into four groups: sedentary control (CTR), sedentary induced (CTR+N-methyl-N-nitrosourea (MNU)), exercised control (EX), and exercised induced (EX+MNU). The exercise protocol involved ladder climbing three times a week for 18 weeks with the load progressively increasing. At the study’s end, blood and histopathological samples were collected and analyzed. Although tumor onset occurred two weeks earlier and incidence was slightly higher in the exercised group (EX+MNU) compared to the control group (CTR+MNU), the mortality rate was lower, and the malignancy was not as aggressive. No systemic inflammation was observed, as the levels of albumin, C-reactive protein (CRP), and interleukin 6 (IL-6) in the MNU groups remained similar to the controls. Exercise has been shown to promote overall health by increasing physical fitness, boosting immunological function, and improving metabolic health. These findings may offer valuable insights into the potential role of resistance training in managing mammary cancer in companion animals. However, further research is required to assess clinical applicability and to establish safe and effective exercise protocols for veterinary oncology.